A GENERAL OVERVIEW OF ARMENIAN-KURT RELATIONS IN OTTOMAN ADMINISTRATIVE STRUCTURE IN THE 19th CENTURY - Melek SARI GÜVEN (Fırat University, 2019)
The 19th century has been a century of change for the Ottoman State primarily in the administrative area and development in military, economic and political terms. Instead of the classical Ottoman administrative structure, which is the state system, the center has begun to work on behalf of empowerment. These transformations, which the Ottoman State has experienced in the administrative area, are all Ottoman in general; Armenian and Kurds have been influenced in many ways by the subject to be examined. In this study, firstly the information about the administrative structure of the Ottoman State will be given and explained how this structure is affected from the change. With this in mind, we will examine how the Armenians and Kurds are influenced by the change in the Ottoman administrative structure and how this effect is reflected in their relations. The Ottomans, following the traditional practice of the Islamic states, have classified communities living in their own countries under the structure of the nation. Even the records of the population in the Ottoman State were kept according to the religion, not the ethnic structure or language group. Armenians were non-Muslims who differed in terms of ethnicity, language and religion. The Kurds, like the Turks, are a Muslim but a group that is different in terms of ethnicity and language. This study will be conducted through five basic points on which communication between these two groups in the Ottoman State is based. These; The influence of the Armenians and the Kurds on the missionary activities carried out in the Ottoman State; establish communities; to be involved in press-publication activities; Activities in the Ottoman State and land problems including village, pasture and plateau problems.